ANALISIS TINGKAT KESEJAHTERAAN RUMAH TANGGA PETANI KOPI DI KECAMATAN PULAU BERINGIN KABUPATEN OGAN KOMERING ULU SELATAN (JASEP, 2017)
Analysis of Household Welfare Coffee Farmers in the district of South OKU District Beringin Island. Purpose of this study was to calculate the income, expenditure and household welfare level of coffee farmers in the district of South OKU District Beringin Island. The research was implemented in December 2016 and January 2017. The sampling method used in this study is Disproportionated Stratified Random Sampling method stratified random lopsided, determined based coating is a sampling system that is divided according to specific layers and each layer has the same number of samples. With sample homogeneity of 1 to 5 hectares of land. The method used in this study is a survey method. Data used in this study included primary data and secondary data. To analyze the level of welfare Household Coffee Farmers used mathematical calculations and tabulations with the indicators BPS Susenas (2015). The average income of the coffee farmer households in the district Beringin Island Ulu Ogan Ogan south Rp 39.5715 million per year, average household spending of coffee farmers in the district Beringin Island Ulu Ogan Ogan Rp 25.7164 million per year., and Based on the results, of the eight indicators Central Bureau of Statistics in 2015 the level of household welfare of coffee farmers in the district Beringin Island South Ulu Ogan Ogan including category prosper as much as 90 percent.